The Effects of Gold Price Increases and Perceptions of Gold as a Safe-Haven Asset on Generation Z’s Interest in Gold Investment: Empirical Evidence from Bone Regency - Nurtasyani Yusni; Andi Fauziah M; Asni Gusmiarni; Otong Karyono (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2026)
Generation Z’s increasing interest to iinvest in gold has not been accompanied by a clear understanding of the factors influencing their investment intention. Rising gold prices and perceptions of gold as a safe-haven asset are presumed to influence investment interest; however, the effects of these factors require further empirical investigation. This study aims to examine the effects of gold price increases and perceptions of gold as a safe-haven asset on Generation Z’s intention to invest in gold. A quantitative approach with survey design was employed. Data was collected through questionnaires administered to 35 Generation Z respondents and analyzed using multiple linear regression with IBM SPSS. The results indicate that gold price increases do not have a statistically significant effect on gold investment intention, whereas perceptions of gold as a safe-haven asset have a positive and statistically significant effect. Simultaneously, gold price increases and perceptions of gold as a safe-haven asset have a statistically significant effect on gold investment interest. These findings indicate that Generation Z’s perception of gold as a safe-haven asset is a more influential factor in shaping investment interest than rising gold prices. Theoretically, this study provides empirical support for the Theory of Planned Behavior and Safe Haven Theory by demonstrating that perceptions of gold’s function as a safe-haven asset play a stronger role in shaping investment interest than price-related factors. Practically, the findings provide valuable insights for financial institutions, investment practitioners, and policymakers in designing financial education and literacy strategies that emphasize gold’s role as a safe-haven asset and store of value, thereby potentially encouraging greater interest to invest in gold among Generation Z.